Advancements in electrocatalytic technologies for metal-supported solid oxide fuel cells: enhancing efficiency and durability for biofuel-powered mobility applications - Ganesan Subbiah; Sasmeeta Tripathy; J. Guntaj; Nandagopal Kaliappan; Beemkumar Nagappan; Devanshu J. Patel; Priya K. Kamakshi (Materials for Renewable and Sustainable Energy)
Abstract This review critically evaluates recent advancements in electrocatalytic technologies aimed at enhancing the efficiency of metal-supported Solid Oxide Fuel Cells (SOFCs) for biofuel-powered mobility applications. The study aims to elucidate the impact of these innovations on the performance, durability, and stability of SOFCs in transportation and portable energy systems. By integrating experimental findings, computational simulations, and practical applications, this work highlights the pivotal role of advanced electrocatalysts in optimizing SOFC functionality. Key developments, such as the incorporation of perovskite-based materials and exsolved nanoparticle catalysts, have demonstrated remarkable improvements in electrochemical performance and operational longevity. Specifically, lanthanum-strontium cobalt ferrite (LSCF)-based cathodes demonstrated a 30% increase in power output and a 25% enhancement in long-term stability under biofuel operating conditions. Furthermore, computational modeling has played a crucial role in refining catalyst designs, achieving a 45% reduction in degradation rates. These advancements underscore the potential of biofuel-driven SOFCs as a sustainable energy solution for transportation. However, future research must address challenges related to scalability, cost-effectiveness, and economic competitiveness to fully realize their practical implementation.